Childbirth experiences in women with polycystic ovary syndrome: A cohort study - Anne Engtrø Husby; Melanie Rae Simpson; Rebecka Dalbye; Marit Larsen; Eszter Vanky; Tone Shetelig Løvvik (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Women with polycystic ovary syndrome (PCOS) have more pregnancy complications like gestational diabetes, hypertension, and preterm labor than other women. Metformin has been used in an attempt to improve pregnancy outcomes. Our study aims to explore childbirth experiences in women with PCOS compared with a reference population. It also explores the potential influence of metformin, obesity, pregnancy complications, and the duration and mode of birth on childbirth experiences. Material and methods This study is a cohort study combining data from two randomized trials conducted in Norway, Sweden and Iceland. The PregMet2 study (ClinicalTrials.gov, NCT01587378) investigated the use of metformin vs. placebo in pregnant women with PCOS. The Labour Progression Study (ClinicalTrials.gov, NCT02221427) compared the WHO partograph to Zhang's guidelines for progression of labor and were used as the reference population. A total of 365 women with PCOS and 3604 reference women were included. Both studies used the Childbirth Experience Questionnaire (CEQ). Main outcome measures were total CEQ score and four domain scores. The CEQ scores were compared using Mann–Whitney U test for women in Robson group 1 with PCOS (n = 131) and reference women (n = 3604). CEQ scores were also compared between metformin‐treated (n = 180) and placebo‐treated (n = 185) women with PCOS, and for different subgroups of women with PCOS. Results There was no difference in total CEQ score between women with PCOS and reference women—Wilcoxon–Mann–Whitney (WMW)‐odds 0.96 (95% confidence interval [CI] 0.78–1.17). We detected no difference in CEQ scores between the metformin‐ and placebo‐treated women with PCOS (WMW‐odds 1.13, 95% CI 0.89–1.43). Complications in pregnancy did not affect CEQ (WMW‐odds 1, 95% CI 0.76–1.31). Higher body mass index (WMW‐odds 0.75, 95% CI 0.58–0.96), longer duration of labor (WMW‐odds 0.69, 95% CI 0.49–0.96), and cesarean section (WMW‐odds 0.29, 95% CI 0.2–0.42) were associated with lower CEQ scores in women with PCOS. Conclusions Women with PCOS experience childbirth similarly to the reference women. Metformin did not influence childbirth experience in women with PCOS, neither did pregnancy complications. Obesity, long duration of labor or cesarean section had a negative impact on childbirth experience.